Organizational Ambidexterity in Family-Managed Firms: The Role of Family Involvement in Top Management. (December 2020) - Kammerlander, Nadine; Patzelt, Holger; Behrens, Judith; Röhm, Christian
Organizational ambidexterity is vital for family firms' long-term success, yet we still lack sufficient insights into the role of family involvement in top management in this context. Building on research on family firm innovation and diversity, we argue there are curvilinear relationships between family involvement in top management and exploration, exploitation, and organizational ambidexterity. We further propose that these (inverse) U-shaped relationships are affected by family CEOs' family-centered noneconomic goals. Multisource data on 109 family-managed firms support most of our hypotheses and provide a nuanced understanding of how diversity within top management affects family firms' innovative behavior.